2020
DOI: 10.3389/fmicb.2020.00394
|View full text |Cite|
|
Sign up to set email alerts
|

A GMC Oxidoreductase GmcA Is Required for Symbiotic Nitrogen Fixation in Rhizobium leguminosarum bv. viciae

Abstract: GmcA is a FAD-containing enzyme belonging to the GMC (glucose-methanol-choline oxidase) family of oxidoreductases. A mutation in the Rhizobium leguminosarum gmcA gene was generated by homologous recombination. The mutation in gmcA did not affect the growth of R. leguminosarum, but it displayed decreased antioxidative capacity at H 2 O 2 conditions higher than 5 mM. The gmcA mutant strain displayed no difference of glutathione reductase activity, but significantly lower level of the glutathione peroxidase activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The GMC oxidoreductase superfamily harbors diverse enzymes with the function of catalyzing a wide variety of redox reactions such as the oxidation of an alcohol moiety to the corresponding aldehyde and the two-step oxidation of an alcohol moiety to the corresponding carboxylic acid [ 34 ]. For example, the choline dehydrogenase catalyzes the two-step oxidation of choline to glycine betaine [ 35 ]. In the current study, we found that capO presented a reverse-U expression pattern in Sphingomonas sp.…”
Section: Resultsmentioning
confidence: 99%
“…The GMC oxidoreductase superfamily harbors diverse enzymes with the function of catalyzing a wide variety of redox reactions such as the oxidation of an alcohol moiety to the corresponding aldehyde and the two-step oxidation of an alcohol moiety to the corresponding carboxylic acid [ 34 ]. For example, the choline dehydrogenase catalyzes the two-step oxidation of choline to glycine betaine [ 35 ]. In the current study, we found that capO presented a reverse-U expression pattern in Sphingomonas sp.…”
Section: Resultsmentioning
confidence: 99%